The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1038/sj.ijo.0801883
|View full text |Cite
|
Sign up to set email alerts
|

Energy and fat intake in obese and lean children at varying risk of obesity

Abstract: OBJECTIVE:This study compared lean children at high risk (HR) and low risk (LR) of obesity and obese children (OB) to assess the relationship between their energy (EI) and fat intake and adiposity. DESIGN: Cross-sectional study of energy and fat intake in children, using 7-day weighed intakes validated by doubly labelled water (DLW) energy expenditure. SUBJECTS: A total of 114 pre-pubertal children, 50 HR (mean AE s.d., 6.7 AE 0.6 y, 25.7 AE 4.8 kg, 21.3 AE 6.6% body fat), 50 LR (mean AE s.d., 6.6 AE 0.8 y, 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
4
8

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(86 citation statements)
references
References 46 publications
4
70
4
8
Order By: Relevance
“…However, when under-reporting was further evaluated among youth categorised into BMI percentile groups, under-reporting was observed only among overweight youth (those with normal BMI had an acceptable EI:BMR ratio of 1?56). The under-reporting of EI among overweight Cree youth is supported by several studies, which found evidence of under-reporting of EI by higher weight children and adults (34,35) . Many factors may occur in late childhood and adolescents that would contribute to the underreporting of EI among higher-weight individuals (36,37) .…”
Section: Discussionmentioning
confidence: 88%
“…However, when under-reporting was further evaluated among youth categorised into BMI percentile groups, under-reporting was observed only among overweight youth (those with normal BMI had an acceptable EI:BMR ratio of 1?56). The under-reporting of EI among overweight Cree youth is supported by several studies, which found evidence of under-reporting of EI by higher weight children and adults (34,35) . Many factors may occur in late childhood and adolescents that would contribute to the underreporting of EI among higher-weight individuals (36,37) .…”
Section: Discussionmentioning
confidence: 88%
“…No presente estudo, verificamos que a ingestão total de energia não estava relacionada ou foi inversamente relacionada com a gordura corporal. Estudos transversais não têm constatado associação entre a ingestão total de energia e excesso de peso ou gordura corporal 31,32 , e, mesmo após o ajuste para o gasto energéti-co, os estudos têm mostrado que as crianças obesas apresentam ingestão de energia menor que as não obesas 33,34 . Quando a ingestão total de energia não está relacionada ou é inversamente relacionada com a gordura corporal, como foi o caso deste estudo, os resultados podem ser explicados segundo algumas possibilidades, por exemplo, indivíduos com peso excessivo controlam a dieta ou comem menos devido aos conselhos da família ou às orientações médicas 35 ou indivíduos com excesso de peso tendem a subestimar a ingestão dietética, consciente ou inconscientemente 36,37 .…”
Section: Resultsunclassified
“…Accumulating evidence suggests that obese individuals tend to consume higher levels of fats, sugars, and proteins than their normal-weight counterparts (e.g., Mai et al, 2011;McGloin et al, 2002;Nicklas, Yang, Baranowski, Zakeri, & Berenson, 2003). Several authors have sought to explain this maladaptive pattern of behavior in terms of food-related evaluations.…”
Section: Irap Food Cognition 2 Abstractmentioning
confidence: 99%